2013
DOI: 10.1038/ncomms2341
|View full text |Cite
|
Sign up to set email alerts
|

A thermoresponsive and chemically defined hydrogel for long-term culture of human embryonic stem cells

Abstract: Cultures of human embryonic stem cell typically rely on protein matrices or feeder cells to support attachment and growth, while mechanical, enzymatic or chemical cell dissociation methods are used for cellular passaging. However, these methods are ill defined, thus introducing variability into the system, and may damage cells. They also exert selective pressures favouring cell aneuploidy and loss of differentiation potential. Here we report the identification of a family of chemically defined thermoresponsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 43 publications
0
78
0
Order By: Relevance
“…To date, at least 16 laminin isoforms are known to exist in mammalian tissues, and most of them have been produced in our laboratory as recombinant proteins 10,11 . Other investigators have reported that recombinant vitronectin 12 , a hydrogel 13 , and a LN-511 fragment 14 can serve as alternatives to Matrigel or feeder cells for culturing of hES cells. However, none of the cell culture substrata allows clonal survival of hES cells without the use of apoptosis inhibitors [15][16][17] or chemically undefined substances 18,19 , and the cells are often passaged in small clumps that can contain a significant proportion of differentiated cells.…”
mentioning
confidence: 99%
“…To date, at least 16 laminin isoforms are known to exist in mammalian tissues, and most of them have been produced in our laboratory as recombinant proteins 10,11 . Other investigators have reported that recombinant vitronectin 12 , a hydrogel 13 , and a LN-511 fragment 14 can serve as alternatives to Matrigel or feeder cells for culturing of hES cells. However, none of the cell culture substrata allows clonal survival of hES cells without the use of apoptosis inhibitors [15][16][17] or chemically undefined substances 18,19 , and the cells are often passaged in small clumps that can contain a significant proportion of differentiated cells.…”
mentioning
confidence: 99%
“…We have recently reported the discovery of a family of thermomodulatable chemically defined (polyacrylate/urethane) hydrogels with high affinity and capacity for long-term support of different human embryonic stem cells in a biomolecularly defined serum-free medium. These have been validated using multiple human embryonic stem cell lines and permit gentle release of cells by transient reduction of ambient temperature to 15°C [5]. This form of substrate can in principle be used to positively or negatively select for an undifferentiated cell phenotype that is not readily achieved through suspension culture, benefiting all aspects of pluripotent stem cell manipulation, from induction to expansion and directed differentiation.…”
Section: "Relatively Unexplored and Equally Pertinent To Small And Momentioning
confidence: 99%
“…Zhang et al [ 43 ] sought to develop a material that would allow stem cells to detach from a surface upon a reduction in temperature rather than using chemical, enzymatic or mechanical methods of removal. To achieve this, an array of 609 unique acrylate and acrylamide polymers was prepared composed of various mixtures of 18 monomer base units.…”
Section: Synthetic Polymersmentioning
confidence: 99%